Multi-LoRa-Based Automatic Drinking Water Transmission System - Sri Indah Rezkika; Adinda Juwita Nasution; Andri Ramadhan; Muhammad Fiza Lubis; Panangian Mahadi Sihombing; Aulia Agung Dermawan (Journal of Applied Informatics and Computing, 2026)
Drinking water transmission systems are needed to fill some reservoirs. However, the water level in each reservoir must be monitored constantly to ensure optimal water transmission. Therefore, a device is needed to monitor the water level and automatically control the transmission system. The purpose of this research is to develop a multi-LoRa-based automatic drinking-water transmission system that provides near-real-time water-level information with an average end-to-end latency of 1.2 seconds, meeting the typical requirements for water-level monitoring in remote reservoirs (acceptable delay < 10 seconds). This study uses a prototype experimental approach, validated with a Laser Distance Meter and sticker meters. The star topology connects several LoRa modules that transmit water-level data without internet access. The purpose system consists of several LoRa modules, water-level sensors, liquid crystal displays (LCDs), solenoid valves, and pressure-switch sensors. A pressure sensor switch is installed on the power-supply side of the water pump, controlling the pump based on the water-pressure difference. The result of this study is that the purpose system can automatically control the water pump to fill several reservoirs based on water-level information from each reservoir. This is evidenced by each solenoid valve opening when the water level is below 10 cm and closing when it reaches 70 cm. So that the water pump can be controlled through a pressure sensor switch. The purpose system can also accurately measure water levels, as evidenced by ME ≤ 0.5 cm, MAPE ≤ 4.4%, RMSE ≤ 0.7 cm, and R² ≥ 0.97. These findings demonstrate the potential of the proposed solution as a cost-effective and reliable solution for remote areas without internet infrastructure.